Process optimization in a stirred tank bioreactor based on CFD-Taguchi method: A case study. (1st September 2019) - Shu, Lei; Yang, Mingjin; Zhao, Hang; Li, Tianfu; Yang, Ling; Zou, Xiang; Li, Yunwu
Abstract: Cleaner aerobic fermentation with high efficiency is of great significance to microbial production. In an aerobic fermentation process, gas holdup and power consumption are main indexes for its performance evaluation. Based on CFD-Taguchi method, effects of control factors of impeller type, gas flow rate and agitation speed on gas holdup and power consumption were studied, by taking pullulan fermentation of Aureobasidium pullulans in a stirred tank bioreactor as a case study. Innovatively, three representative viscosity stages and their corresponding viscosities were defined according to viscosity change during fermentation, so as to quantitatively optimize the fermentation process. By range analysis and analysis of variance, effects of control factors and their significant levels on fermentation performance were obtained so as to optimize the fermentation system. All control factors were significant at low viscosity stage, and insignificant at stages of medium and high viscosity except for gas flow rate at high viscosity stage ( p  < 0.05). Impeller of bent blade disc turbine had the highest comprehensive evaluation index during the fermentation process, with the optimal agitation speed and gas flow rate 400 rpm and 7.8 L/min at low viscosity stage, and 400 rpm and 7.8 L/min at stages of medium and high viscosity. Highlights: Process optimization to improve gas holdup and power consumption. Three viscosity stages of pullulan fermentation of Aureobasidium pullulans. Structure and parameter optimization of stirred tank bioreactor by CFD-Taguchi method. Bent blade disc turbine with 400 rpm having the best fermentation performance. The optimal gas flow rates 5.4 L/min at low viscosity stage and 7.8 L/min otherwise.